Carbohydrate-hydroxymethylfurfural-amine adhesives: Chemorheological analysis and rheokinetic study. (28th September 2021) - Thoma, Catherine; Solt-Rindler, Pia; Sailer-Kronlachner, Wilfried; Rosenau, Thomas; Potthast, Antje; Konnerth, Johannes; Pellis, Alessandro; van Herwijnen, Hendrikus W.G.
Abstract: Carbohydrates as a component in adhesive formulations have been reported for many years. A rapid cure at moderate temperatures is a remaining challenge in the development of renewable adhesives. Rheology provides insight into all stages of structure formation of a cured polymer. This work analyses the curing of carbohydrate-amine adhesives with and without the addition of 5-hydroxymethylfurfural (HMF) as a biomass-derived key reactant in adhesives. Isothermal and non-isothermal rheological measurements were performed to characterize i) the rheology of the prepolymer, ii) the initial stages of curing, iii) the sol-gel transition, and iv) general rheokinetics. The viscosity profile was described by empirical models and showed a deviation from homogeneous curing. Rheokinetic analysis using isoconversional methods and Arrhenius plots showed that HMF reduces the activation energy of the curing reaction. The addition of 5 mol.-% HMF (based on starting fructose content) increases the reactivity by lowering the activation energy of the curing. Graphical abstract: Image 1 Highlights: Rheological characterization of carbohydrate-amine adhesives. Chemorheological analysis showed deviation from homogeneous curing. Addition of Hydroxymethylfurfural has positive effect on curing reaction. Isoconversional methods based on rheological data showed multi-step curing reaction.